Fear at Delivering Presentations: Relations to Age - Vanja Šimičević; Višnja Jurić; Tamara Ćurlin (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Virtual Conference, 10-12 September 2020, 2020)
Highly polished presentations skills became prevalent communication technique in various academic and business disciplines fields. Presentation competencies became not just preferable, but indispensable for graduates on the employment market. The fear is the main reason, which decreases the presentation's delivering quality, so the teachers include presentations into curricula from early stages of educations. Scholars continuously develop techniques and methods, which reduce student stress and anxiety during a presentation performance. However, different methods are effective for different types of fears and anxieties. The purpose of this paper is to establish is their connection between different age groups and different types of fear. The research was undertaken on a sample of 495 students from the Faculty of Economics and Business in Zagreb, and the correspondence analysis was used to examine the data. The evidence from this study confirmed that the different age groups are more prone to different kind of fears, and it provided a deeper understanding of the origins of student presentation fears. The results could be beneficial both for scholars who can use this paper for developing further investigations and for practitioners who work with students, for developing specific methods for different kind of fears and age groups.
Keywords: A23; 330; presentation skills; fear; public speech; correspondence analysis; education